2018
DOI: 10.1080/01616412.2018.1428389
|View full text |Cite
|
Sign up to set email alerts
|

A modified Essen Stroke Risk Score for predicting recurrent ischemic stroke at one year

Abstract: Objective The Essen Stroke Risk Score (ESRS) is widely used to predict the risk of recurrent ischemic stroke but may not have sufficient discriminatory ability for predicting early recurrence. In this study, we developed a modified ESRS for predicting recurrent ischemic stroke at one year based on Chinese population. Methods Eight hundred and three consecutive patients were included in the study. We performed a univariate analysis to investigate the effect of previously identified risk factors on recurrent str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
0
5
1
Order By: Relevance
“…Despite advancements in medical therapy, the risk of recurrent ischemic stroke treated with optimal medication therapy remains between 6.5% and 20% per year in Asia. [18][19][20][21] The incidence rate per 100 person-years of recurrent stroke in our study (0.543) was lower than that reported by Ogata and Omori (6.486 and 10.672, respectively).…”
Section: Recurrence Stroke After Ablation In Patients With Prior Stcontrasting
confidence: 73%
“…Despite advancements in medical therapy, the risk of recurrent ischemic stroke treated with optimal medication therapy remains between 6.5% and 20% per year in Asia. [18][19][20][21] The incidence rate per 100 person-years of recurrent stroke in our study (0.543) was lower than that reported by Ogata and Omori (6.486 and 10.672, respectively).…”
Section: Recurrence Stroke After Ablation In Patients With Prior Stcontrasting
confidence: 73%
“…It is extremely important that clinicians are able to predicate the risk of END in patients with acute ischemic stroke in the early stages in order to choose an appropriate treatment method. Although many predictive models have been developed to project short-term or long-term functional outcomes of the disease and the risk of recurrence in patients (29)(30)(31), the WORSEN score (8) was the only one specifically developed for detection of END in acute ischemic stroke patients. Our study aimed to externally validate the WORSEN score in our population, and our findings indicated that it had a good predictive value for severe END with a sensitivity of 70.91%, specificity of 83.95%, and an the AUC of WORSEN score of 0.82 (95%CI 0.78-0.86).Fittingly, our findings were in line with prior studies.…”
Section: Discussionmentioning
confidence: 99%
“…Brain tissue ischemia and hypoxia cause irreversible damage to some nerve functions. Under the combined action of multiple risk factors, recurrent stroke causes the brain tissue to suffer from hypoperfusion and oxidative stress again, further aggravating the nerve injury [ 20 ]. However, it has not been clarified whether the risk factors for recurrent and first-ever stroke are completely similar, and there are few studies on the severity and short-term prognosis of recurrent ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%